Study of alexithymia among people with low distress tolerance compared to non-clinical sample - Sajjad Heydarian; Edris Azami; Afshar Sahraei; Akbar Mohammadi; Mohsen Rezaei (Shahid Beheshti University of Medical Sciences, 2017)
Background: Alexithymia is a personality construct described as an asymptomatic clinical disability to identify and describe individual feelings. Individuals with alexithymia have difficulties regarding distress tolerance. The present research aimed at studying alexithymia among people with low distress tolerance in comparison to non-clinical sample. Methods: The study population consisted of all male employees working for General Education Office of Kermanshah Province, Iran. A total of 300 individuals from among these employees were selected based on Morgan table using multistep clustering method. Demographic data questionnaire, Toronto alexithymia scale, and distress tolerance questionnaire were used for data collection. Results: Mean (SD) score for tolerance, attracting, Assessment and Regulation were 7.3 (2.74), 8.4 (3.20), 16.8 (4.99), and 6.7 (2.63), respectively, in the normal group and 22.54 (6.07), 17 (4.28), 30.67 (6.65), and 30.50 (74.6) in the group with low distress tolerance. independent t-test showed that low distress tolerance group had significantly higher score regarding tolerance, absorption, evaluation, and regulation in comparison with the normal group (P<0.001). Conclusion: Findings of the present study can help psychologists and counsellors to pay more attention in alexithymia among people with Low Distress Tolerance to help them for better adaptability and confrontation ability against life difficulties such as distress, and ultimately for better health.